ANALISIS FAKTOR DETERMINAN EFISIENSI NILAI BED OCCUPANCY RATIO: FISHBONE ANALYSIS - Tri Lestari; Isa Tri Wahyuni (Program Studi Perekam Medis & Informasi Kesehatan, 2019)
One indicator of the fulfillment of health services to the community, especially in hospitals, was the calculation of the Bed Occupancy Rate (BOR). Factors that caused inefficient BOR need to be analyzed. This study aimed to analyze the factors causing inefficient BOR through fishbone analysis. This study was a qualitative descriptive study conducted at Surakarta City Hospital in February - June 2019. The subjects of this study were medical record officers, inpatient registration, reporting, ward head, doctor providing services. Data is taken by interview method and observation checklist. Data were analyzed using fishbone analysis The results of this study indicate that the factors that cause inefficient BOR values are Method (doctor's visit schedule has not been obeyed and SOP related to CP has not been implemented), Machine (lack of TT availability, system error, and meeting forums are less effective ), Man (human resources) (lack of neurosurgeons, doctors' uncertainty in visiting, part-time doctors), Materials (materials) (recapitulation data is not available LD data items, SHRI only contains a 1 day resume of activities in the form of numbers ), Money (funds) (There is no funding for rewarding), environment (damaged road access and less strategic location). Fishbone diagram inefficient BOR values are caused by the Man factor (human resources) and the Machine factor (machine).